2012
DOI: 10.1590/s0001-37652012005000050
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the myenteric neuronal population and subpopulation of the duodenum of adult wistar rat fed with hypoproteic chow

Abstract: The effects of severe protein malnutrition (4%) on myenteric neurons of Wistar rat duodenum, in relation to a standard 22%-protein diet for rodents, were assessed in this study. Segments of the duodenum from 10 rats from each nutritional group were submitted to the elaboration of whole mounts -5 stained with Giemsa to determine the total population of myenteric neurons and the others stained by a histochemical method to detect nervous cells through the NADPH-diaphorase enzyme activity for studying the subpopul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Regarding the external muscle, we verified that it underwent virtually no morphological changes due to the food restriction imposed on the DRG. This is indicative that these rats were probably not protein-energy malnourished, since atrophy of intestinal smooth muscle is common in these cases, as a compensatory mechanism due to lower intake of amino acids in the diet (De Azevedo et al, 2007;Moreira et al, 2008;Hermes et al, 2008;Franco et al, 2010;Sant'Ana et al, 2012;De Lima et al, 2012).…”
Section: Duodenummentioning
confidence: 99%
“…Regarding the external muscle, we verified that it underwent virtually no morphological changes due to the food restriction imposed on the DRG. This is indicative that these rats were probably not protein-energy malnourished, since atrophy of intestinal smooth muscle is common in these cases, as a compensatory mechanism due to lower intake of amino acids in the diet (De Azevedo et al, 2007;Moreira et al, 2008;Hermes et al, 2008;Franco et al, 2010;Sant'Ana et al, 2012;De Lima et al, 2012).…”
Section: Duodenummentioning
confidence: 99%
“…to stain the total myenteric neuron population, the present study used the Giemsa technique, with no significant differences between treatments, as well as with the control group (table 1). According to BARBoSA (1978), the Giemsa staining technique, which uses the methylene blue dye in digestive tract membrane preparations, can be used as one of the available methods to evaluate the total myenteric neuronal population due to the affinity of the dye for acid structures in nerve cells (SANt'ANA et al, 2012). GÓIS et al (2016) reported that the polyribosomes of all neurons can be stained by the Giemsa technique.…”
Section: Resultsmentioning
confidence: 99%
“…Conditions that cause functional damage to the digestive tract have been induced in vivo to analyze the myenteric plexus. Morphometric and quantitative parameters of myenteric neurons were analyzed in Parkinson's disease, Crohn's disease, toxoplasmosis (Hermes-Uliana et al 2011, Anderson et al 2007, Boyer et al 2007, malnutrition and during caloric or protein restriction (Sant'Ana et al 2012, Silva-Porto et al 2012Natali et al 2005, Cowen et al 2000, diabetes (Fregonesi et al 2005, Zanoni et al 2003, and during aging (Gagliardo et al 2008, Marese et al 2007, Phillips et al 2003, among other conditions.…”
Section: Introductionmentioning
confidence: 99%